Analisis Ekonomi Usaha Tani Padi Di Kecamatan Bunga Raya Kabupaten Siak - Windy Wahyuni; Siswanto Siswanto; Rian Tri Komara Iriana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This study aims to determine the cost of production facilities, wages, and other expenses in one year to obtain the feasibility rate of rice farming in the Bunga Raya District. This research was conducted in 5 villages in Bunga Raya sub-district which have a fairly advanced farmer group. The collected data in this study are primary and secondary data analyzed using the BCR (Benefit Cost Ratio) concepts. Result research shows that rice farming run by farmers in Bunga Raya District is overall feasible to continue, but there are several inhibiting factors that cause a decrease in production. Based on the research of average farmers' net income is Rp. 16,000,000 to Rp. 20,000,000 for planting seasons (four months). Because the production and income of farmers start to increase with the development of irrigation facilities, this raises the interest of farmers who once converted rice fields into oil palm plantations to re-cultivate rice fields for rice farming. Keyword: Small Water, Bunga Raya, BCR